Food, Masculinity and Gender-based Violence in Sally Andrew's Recipes for Love and Murder (2015) - van Heerden, Neil (Journal of literary studies (Pretoria, South Africa), 2021)
This article offers a reading of Sally Andrew's debut murder mystery novel, Recipes for Love and Murder: A Tannie Maria Mystery (2015), from the angle of critical food studies. The article explores how the novel's depiction of food relates to notions of masculinity and power against the backdrop of widespread gender-based violence in South Africa today. I argue that the protagonist and narrator's reverent, restorative relationship with food represents a gentle yet powerful feminine counternarrative to the violent masculinities of subjugation embodied in Fanie's dogmatic religious ideology, Dirk's oppressive military indoctrination, and Cornelius's cruel hunting practices. Beyond providing mere escapism, this supposedly "popular" novel can therefore be seen as delivering sharp, timely social commentary.